Raynaud phenomenon secondary to beta-blocker intake: case report (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Raynaud’s Phenomenon (RF) is a transient ischemia of the extremities. It can be primary or secondary to certain diseases or drugs, such as beta blockers. The prevalence of this phenomenon can vary between 7% and 14.7%. The pathophysiology is little known. Using beta blockers with greater affinity for beta-1 adrenoreceptors, such as bisoprolol, will not protect against the development of RF.Case description: The case of a 64 years old female who resorted to several consultations at the primary care health center and to other medical specialties, due to progressive pain and edema of the hands, change in the colour of the fingers, and ulcerated wounds, with onset after starting to take bisoprolol and exposure to cold (winter). After carrying out several tests and treatments for pathologies such as erythema pernio and carpal tunnel syndrome (CTS), without success, treatment with bisoprolol was suspended, with resolution of the symptoms. The diagnosis of RF secondary to beta-blocker intake was assumed.Comment: RF is complex, multifactorial, and not yet completely understood. RF secondary to the use of beta blockers is a poorly described effect of a relatively safe drug, widely used in clinical practice, which may hamper the diagnosis. The coexistence of bilateral CTS is in line with the greater prevalence of this pathology in individuals with RF, who may also have initially delayed diagnosis. Low temperatures and clinical similarities may justify consideration of erythema pernio. Observation by several doctors from different specialties, at the patient's initiative, may also have made diagnosis and follow-up more difficult. Therefore, this report seeks to raise awareness of the diagnosis of RF secondary to beta blocker intake, especially in winter, due to possible confusion with erythema pernio. Also, it reinforces the importance of adequate medical follow-up.
Keywords: Raynaud phenomenon; Adrenergic beta-antagonists; Chilblains; Case report